The use of ferrites at microwave frequencies - Thourel, L. (Leo) (International series of monographs on electronics and instrumentation ;, 1964)
The Use of Ferrites at Microwave Frequencies describes the applications of ferrites at microwave frequencies and the apparatus involved. Topics covered range from the properties of ferrites to gyromagnetic and non-reciprocal effects, ferrite isolators, circulators, and modulators. The use of ferrites in variable frequency filter cavities is also discussed. Mathematical explanations are reduced to the strict minimum and only the results of calculations are indicated. This book consists of seven chapters and opens with a review of the theory of magnetism, touching on subjects such as the BOHR m.